Penentuan Tingkat Kepuasaan Pelanggan dengan Pengambilan Keputusan Menggunakan Metode Fuzzy Tsukamoto (Studi Kasus:Toko Emas Murni Padang) - kenny yulianti; Yusmet Rizal (UNIVERSITAS NEGERI PADANG, 2022)
Buyer satisfaction is a human feeling that is described in the variable of words. This variable is not rigid so that its value cannot be calculated with certainty. So to feel directly the value of these variables can use fuzzy logic. Research data obtained from the results of distributing questionnaires based on indicators of service quality, product quality and price. The stages of the Tsukamoto fuzzy method are determining the fuzzy set for the input and output variables, determining the implication function, forming fuzzy logic rules, and performing defuzzification with a weighted average. Based on the results of the value of customer satisfaction obtained in subject 1 with a value of service quality 14, product quality 14 and price 10, the results obtained with a satisfaction value of 49.88.